POTENSI ANTIFERTILITAS EKSTRAK TEH HITAM PADA MENCIT (Mus musculus L.) JANTAN - DELFITA, RINA (IAIN Batusangkar, 2014)
The effects of black tea extract on mice fertility was studied in twenty four (n=24) sexually matured male mice. Mices were randomly divide into four (4) groups of six (6) mices per group. The experimental groups ware treated as follows: Group I treated with no received treatment, Group II with 1,25 %, Group III with 2,5 %, and Group IV with 5 % black tea extract. The extract was orally administered 1 ml/100 g body weigh for 35 days. The epididymis weight, sperm count, motility, viability and normal sperm morphology changes were determined. The epididymis weight, sperm count, motility, viability and normal sperm were decreased. Treatment with highest dose 5 % of the extract resulted in a significant decreased when compared to the control. Result showed that black tea extract has potential for use as antifertility for animal in future.Key words: black tea extract, mice fertility